World Heart Federation Roadmap for Digital Health in Cardiology - Jasper Tromp; Devraj Jindal; Julie Redfern; Ami B. Bhatt; Tania Séverin; Amitava Banerjee; Junbo Ge; Dipti Itchhaporia; Tiny Jaarsma; Fernando Lanas; Francisco Lopez-Jimenez; Awad Mohamed; et al. (Ubiquity Press, 2022)
More than 500 million people worldwide live with cardiovascular disease (CVD). Health systems today face fundamental challenges in delivering optimal care due to ageing populations, healthcare workforce constraints, financing, availability and affordability of CVD medicine, and service delivery. Digital health technologies can help address these challenges. They may be a tool to reach Sustainable Development Goal 3.4 and reduce premature mortality from non-communicable diseases (NCDs) by a third by 2030. Yet, a range of fundamental barriers prevents implementation and access to such technologies. Health system governance, health provider, patient and technological factors can prevent or distort their implementation. World Heart Federation (WHF) roadmaps aim to identify essential roadblocks on the pathway to effective prevention, detection, and treatment of CVD. Further, they aim to provide actionable solutions and implementation frameworks for local adaptation. This WHF Roadmap for digital health in cardiology identifies barriers to implementing digital health technologies for CVD and provides recommendations for overcoming them.